Aplikasi Pembayaran SPP Terintegrasi Midtrans Payment Gateway Dan WhatsApp Gateway Berbasis Mobile Web Studi Kasus SMK Al Fatah Banjarnegara - Muhammad Khoerul Anwar; Tri Haryanti; Luthfi Nur Azizah (CV. ITTC INDONESIA, 2025)
The research was conducted at SMK Al-Fatah Banjarnegara, which previously relied on a manual system for recording and delivering payment information. The aim of this study is to develop a tuition payment application based on mobile web, integrated with Midtrans Payment Gateway for online transactions and WhatsApp Gateway as a payment reminder medium. Data collection methods included interviews, observations, and the distribution of Likert scale questionnaires to 42 respondents. The evaluation was carried out through black box testing and user satisfaction analysis using questionnaires. This study employed the Research and Development (R&D) method with a qualitative descriptive approach to explore user needs and design a technology-based solution. The application development followed the ADDIE model, consisting of five systematic stages: Analysis, Design, Development, Implementation, and Evaluation. System design was created using UML diagrams (Use Case, Activity, Sequence, and Class Diagram). The application was developed using the PHP programming language and MySQL as the database, built in the XAMPP with Visual Studio Code editor. The interface design was created using Figma, and the diagrams were made using Draw.io. Based on the evaluation results of the questionnaire, the application received a rating of 93% from respondents, which is categorized as “very good”.